Budaya Petung Dalam Masyarakat Jawa : Kajian Antropologi - PANA PRAMULIA (Universitas PGRI Adi Buana Surabaya, 2019)
Javanese society is identical with mysticism. Everything that Javanese people do cannot be separated from the physical and metaphysical worlds. The physical and metaphysical worlds are interrelated, as these would form harmony of life between living beings and God. The harmony built by the Javanese community is not only for the people, but also for the whole living things in the world. That is what the Javanese community call the bebrayan agung. One of the patterns carried out by Javanese people to lead a bebrayan agung is by practicing the culture of petung. This culture is not only a calculation of life behavior, but also as a dialectic between humans and fate and the universe. Many people perceive that petung culture is only a prophecy, but in fact, it teaches wisdom ​​as a way of life. This is due to that the culture of Petung or Petungan in Javanese society is closely related to birthdays, pasaran, and neptu. All of these have to do with birth, sustenance, matchmaking, illness, and death. In short, everything is strung together based on the standard calculations contained in the primbon and the Javanese calendar. In this regard, Petung culture is a mathematical civilization technology that uses calculations of numbers in the Javanese calendar.This study, therefore, is focused on exploring the culture of petung in Javanese society framed within the anthropological analysis.